2010
DOI: 10.1002/adma.201000520
|View full text |Cite
|
Sign up to set email alerts
|

Specific Protein Detection Using Thermally Reduced Graphene Oxide Sheet Decorated with Gold Nanoparticle‐Antibody Conjugates

Abstract: A highly sensitive and selective field‐effect transistor biosensor using thermally reduced graphene oxide (TRGO) sheet decorated with gold nanoparticle‐antibody conjugates is demonstrated. Probe antibody (anti‐Immunoglobulin G) is labeled on the surface of the TRGO sheet through gold nanoparticles and electrical detection of the protein binding (Immunoglobulin G and anti‐Immunoglobulin G) is accomplished by FET and dc measurements.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
316
1

Year Published

2012
2012
2019
2019

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 462 publications
(323 citation statements)
references
References 46 publications
2
316
1
Order By: Relevance
“…Recently, graphene based materials have been widely studied for sensing applications, e.g., in strain sensors,52, 141, 142, 143 temperature sensors,144 biosensors,145, 146, 147, 148 and gas sensors,72, 81, 149 as shown in Figure 19 . Nanographene films grown by PECVD have been transferred onto polydimethylsilxane (PDMS) with prestrain 51.…”
Section: Applications Of Graphene Grown By Pecvdmentioning
confidence: 99%
“…Recently, graphene based materials have been widely studied for sensing applications, e.g., in strain sensors,52, 141, 142, 143 temperature sensors,144 biosensors,145, 146, 147, 148 and gas sensors,72, 81, 149 as shown in Figure 19 . Nanographene films grown by PECVD have been transferred onto polydimethylsilxane (PDMS) with prestrain 51.…”
Section: Applications Of Graphene Grown By Pecvdmentioning
confidence: 99%
“…Mao et al 74 demonstrated a specific protein detection biosensor using reduced GO sheets decorated with Au nanoparticle-antibody conjugates (Figure 6a). The response of the sensor increases with the increase of protein concentrations and saturates at 0.02 mg ml À1 .…”
Section: Grapheneàstrategies To Increase Sensitivitymentioning
confidence: 99%
“…Furthermore, the HRG/Au based nanocomposites have been applied as FET (field effect transistor) biosensors for the detection of proteins. 533,534 The FET biosensor was fabricated by suspending thermally reduced graphene oxide (TRG) sheets above the substrates across the gold electrode. When the protein was introduced, it induced changes in the electrical characteristics of the device, which were investigated by FET and direct current measurements.…”
Section: Biosensorsmentioning
confidence: 99%